Diffusion tensor imaging of white matter and correlates to eye movement control and psychometric testing in children with prenatal alcohol exposure. Issue 1 (13th September 2016) - Paolozza, Angelina; Treit, Sarah; Beaulieu, Christian; Reynolds, James N.
Abstract: Prenatal alcohol exposure (PAE) can cause central nervous system dysfunction and widespread structural anomalies as detected by magnetic resonance imaging (MRI). This study focused on diffusion tensor imaging (DTI) of white matter in a large sample of PAE participants that allowed us to examine correlations with behavioral outcomes. Participants were confirmed PAE ( n = 69, mean age = 12.5 ± 3.2 years) or typically developing control children ( n = 67, mean age = 12.1 ± 3.2 years) who underwent brain MRI, eye movement tasks, and psychometric tests. A semi‐automated tractography method extracted fractional anisotropy (FA) and mean diffusivity (MD) values from 15 white matter tracts. The PAE group displayed decreased FA compared with controls in multiple tracts including 3 corpus callosum regions, right corticospinal tract, and 3 left hemisphere tracts connecting to the frontal lobe (cingulum, uncinate fasciculus, and superior longitudinal fasciculus). Significant group by sex interactions were found for the genu, left superior longitudinal fasciculus, and the left uncinate, with females in the PAE group exhibiting lower FA compared with control females. Correlations were found between DTI and eye movement measures in the control group, but these same relationships were absent in the PAE group. In contrast, no correlations were found between DTI and any of the psychometric tests used in this study. These findings support the hypothesis that measures of eye movement control may be valuable functional biomarkers of the brain injury induced by PAE as these tasks reveal group differences that appear to be linked to deficits in white matter integrity in the brain. Hum Brain Mapp 38:444–456, 2017 . © 2016 Wiley Periodicals, Inc.